PERLINDUNGAN HUKUM PARA PIHAK DALAM PERJANJIAN KREDIT ONLINE (P2P LENDING) STUDI KASUS PT VCARD TECHNOLOGY INDONESIA - I Made Wirya Darma; Putu Gede Andre Putra Jadnya (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
The development of digital economy has led people to adapt to the use of services in information-technology-based loan or peer-to-peer lending. In early 2019, the V-loan case attracted attention of many people. The case has made debtors depressed, removed from their own houses, etc. Some debtors even were fired from works. In a case, the loan provider misused debtors’ personal data in debtors’ cell phones. The loan provider created WhatsApp groups containing all debtors’ contacts, including the debtors. Then, they uploaded pornographic content. Their objective was to defame debtors. Parties involved in loan agreement should adhere rules and arrange for reasonable loan. To discuss this matter, it is necessary to review agreement based on the Law on Electronic Information and Transaction and the Regulation of Financial Services Authority number 77 of 2016. The study focused on legal protection of parties involving in P2P lending activities. The credit agreement of peer-to-peer lending is considered valid if it is based on Article 47 of the Government Regulation number 82 of 2016. Standard contract must be based on Article 20 of the Regulation of Financial Services Authority number 77 of 2016. Electronic signature is also required based on Article 41 of the Regulation. In addition, the application of information technology and electronic transactions must be carried out based on the principles of legal certainty, benefits, good faith, and the freedom of choice of technology based on Article 3 of Law Number 19 of 2016. Principles and objectives are fundamental elements of legal certainty. Therefore, organizer and the government must protect user of peer-to-peer lending.Perlindungan Hukum Para Pihak dalam Perjanjian Kredit Online (P2P Lending) Studi Kasus PT Vcard Technology Indonesia AbstrakPerkembangan ekonomi digital menuntun masyarakat terhadap adaptasi penggunaan layanan dalam kegiatan pinjam meminjam uang berbasis teknologi informasi atau P2P lending. Kasus yang menyorot perhatian di awal tahun 2019 ialah kasus Vloan. Kasus ini membuat debiturnya tertekan, diusir dari rumah, bahkan sampai kehilangan pekerjaan dengan menyalahgunakan data pribadi yang ada pada ponsel debitur dengan cara membuat grup whatsapp berisi seluruh kontak pada ponsel debitur termasuk debitur itu sendiri kemudian melakukan penagihan yang tidak beretika dengan menyebarkan konten pornografi dan pencemaran nama baik. Para pihak seharusnya mengikuti aturan yang berlaku dan penyelenggara menghindari praktik penagihan yang tidak wajar. Untuk membahas hal tersebut perlu ditinjau perjanjian yang mengacu pada UU ITE dan POJK 77/2016 dan perlindungan hukum para pihak terhadap kegiatan P2P lending. Keabsahan perjanjian kredit P2P lending dinyatakan sah apabila memenuhi ketentuan yang diatur di dalam Pasal 47 PP 82/2016, kontrak baku yang disediakan oleh penyelenggara paling sedikit memuat ketentuan yang diatur di dalam Pasal 20 POJK 77/2016, dan tanda tangan elektronik juga wajib dipergunakan sesuai dengan ketentuan Pasal 41 POJK 77/2016. Selain itu, pemanfaatan teknologi informasi dan transaksi elektronik wajib dilaksanakan berdasarkan asas kepastian hukum, manfaat, itikad baik, dan asas kebebasan memilih teknologi/netral teknologi yang diatur di dalam Pasal 3 UU 19/2016, sebab asas dan tujuan merupakan kunci dari perbuatan hukum yang andal, khususnya dalam kegiatan P2P lending yang beroperasi menggunakan teknologi informasi dan komunikasi dan Perlindungan hukum pengguna tidak akan dapat dilindungi ketika tidak didukung oleh peran para pihak seperti penyelenggara, pengguna, dan pemerintah.Kata Kunci: Fintech, P2P Lending, Perlindungan Hukum https://doi.org/10.22304/pjih.v6n3.a5